2021
DOI: 10.1016/j.avsg.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Evaluation of COVID-19 Patients With Peripheral Arterial Thromboembolism: Does Clot Composition Make Any Sense?

Abstract: Background Coronavirus disease 2019 (COVID-19) causes thromboembolic complications during or post-infection period despite a lack of conventional risk factors. The study aims to learn fundamental changes in COVID-19 patients who underwent embolectomy in terms of clinical characteristics and clot composition. Methods In a retrospective cohort study design, we evaluated 21 patients who underwent embolectomy in our clinic between March 12, 2020, and December 31, 2020. Demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 34 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…The quality of studies is shown in Table 2. Four studies [6,9,10,13] were of good quality, and six studies [4,5,[14][15][16][17] were of poor quality.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…The quality of studies is shown in Table 2. Four studies [6,9,10,13] were of good quality, and six studies [4,5,[14][15][16][17] were of poor quality.…”
Section: Study Qualitymentioning
confidence: 99%
“…Six studies [4][5][6]9,13,17] mentioned the re-thrombosis rate in the revascularized limb in ALI patients with COVID-19. The data were pooled to do the analysis.…”
Section: Re-thrombosismentioning
confidence: 99%
See 2 more Smart Citations
“…NET plays a key role in immunothrombosis and was demonstrated to be consistently increased in COVID-19 and linked to disease severity (26, 27). Indeed, complications such as acute arterial thromboembolism have been reported in COVID-19 (28) and inflammatory cells are prominent in arterial thromboembolic material from COVID-19 patients (29). However, recent data did not provide evidence for classic thrombotic microangiopathy in COVID-19 (22) which is in agreement with our observation that higher cfDNA concentrations were not associated with thromboembolism.…”
Section: Discussionmentioning
confidence: 99%